Factors Affecting the Mortality of Patients in Critical Condition with Coronavirus Disease-2019 in the Intensive Care Unit - Osman Uzundere; Cem Kıvılcım Kaçar; Meral Erdal Erbatur; Mehmet Salih Gül; Mesut Akgündüz; Zeki Korhan; Ömer Can (Galenos Yayinevi, 2021)
Objective:This study aimed to determine the factors affecting the mortality of patients in critical condition with coronavirus disease-2019 (COVID-19) in the intensive care unit (ICU).Materials and Methods:We included a total of 445 patients who are admitted in the ICU due to COVID-19. Patients were divided into two groups-those who survived and those who died during the ICU follow-up-and their demographic, clinical and laboratory characteristics were compared. Factors affecting mortality were also determined.Results:Older age, high Kidney Disease: Improving Global Outcome (KDIGO) stage and Sequential Organ Failure Assessment (SOFA) scores at first admission to the ICU, high neutrophil/lymphocyte ratio, high D-dimer levels, low bicarbonate (HCO3) values and high lactate dehydrogenase (LDH) and creatinine levels were determined as independent risk factors for mortality in patients in critical condition with COVID-19 admitted in the ICU. Particularly, a substantial relationship was observed between the KDIGO stage and mortality during the ICU admission.Conclusion:Age, KDIGO stage and SOFA scores at first admission, neutrophil/lymphocyte ratio and D-dimer, HCO3, LDH and creatinine levels were independent risk factors for mortality in patients in critical condition with COVID-19 admitted in the ICU.